Respuesta :
Answer:
(a) 64 feet per second.
(b) -64 feet per second.
Step-by-step explanation:
We have been given that the height S after t seconds is given by the equation [tex]S(t) = 36+128t-16t^2[/tex].
(a) We are find the average velocity in the first 4 seconds after it is thrown.
We will average rate change formula to solve our given problem.
[tex]\text{Average rate change}=\frac{f(b)-f(a)}{b-a}[/tex]
[tex]\text{Average velocity in first 4 seconds}=\frac{S(4)-S(0)}{4-0}[/tex]
Let us find S(4) and S(0) as:
[tex]S(4)=36+128(4)-16(4)^2[/tex]
[tex]S(4)=36+512-16(16)[/tex]
[tex]S(4)=36+512-256[/tex]
[tex]S(4)=292[/tex]
[tex]S(0)=36+128(0)-16(0)^2[/tex]
[tex]S(0)=36[/tex]
[tex]\text{Average velocity in first 4 seconds}=\frac{292-36}{4}[/tex]
[tex]\text{Average velocity in first 4 seconds}=\frac{256}{4}[/tex]
[tex]\text{Average velocity in first 4 seconds}=64[/tex]
Therefore, the average velocity is first 4 seconds would be 64 feet per second.
(b). [tex]\text{Average velocity in next 4 seconds}=\frac{S(8)-S(4)}{8-4}[/tex]
[tex]S(8)=36+128(8)-16(8)^2[/tex]
[tex]S(8)=36+1024-16(64)[/tex]
[tex]S(8)=36+1024-1024[/tex]
[tex]S(8)=36[/tex]
[tex]\text{Average velocity in next 4 seconds}=\frac{36-292}{4}[/tex]
[tex]\text{Average velocity in next 4 seconds}=\frac{-256}{4}[/tex]
[tex]\text{Average velocity in next 4 seconds}=-64[/tex]
Therefore, the average velocity is next 4 seconds would be -64 feet per second.